Neuroimaging and electroencephalographic (EEG) methods for investigating neural circuits in mental disorders - Murakami Junior, Mario Minor; Hoexter, Marcelo Q.; Shephard, Elizabeth (Revista de Medicina, 2019)
It is increasingly recognised that dysfunction in neural circuits plays a key role in the neurobiological basis of mental disorders. The efficacy of pharmacological and behavioural treatments for mental disorders could therefore be improved by targeting dysfunctions in neurocircuits. However, to achieve this, a better understanding of the specific alterations in neural circuits involved in different mental disorders is required. Such understanding can be acquired by using advanced neuroscience methods to examine the pathways and function of neurocircuits in both typically developing individuals and in those with mental disorders. This article provides an overview of currently available neuroscience methods of investigating neural circuits, including advantages and limitations of different techniques, and highlights the importance of using multi-modal imaging in future research